(untitled) (Historia, 2021)
Historical studies are challenged by post modernist argumentations in the humanities radically criticizing the idea of method and objectivity and the concept of history as a comprehensive reality in the temporal change of the human world. The argumentation of this criticism is considered and partly accepted. On the other hand the specifically modern concept of history as it is realized in the tradition of historical studies as an academic discipline is picked up and critically directed against the criticism of post modernism. On the level of an explicit theory of historical studies both argumentations are mediated and synthesized. This is done in respect to the recent debate on the role of memory in the humanities in general and historical thinking in specific. So, finally, a new concept of historical studies as an academic discipline is proposed.